2001
DOI: 10.1074/jbc.m009988200
|View full text |Cite
|
Sign up to set email alerts
|

The Crystal Structures of Apo and Complexed Saccharomyces cerevisiae GNA1 Shed Light on the Catalytic Mechanism of an Amino-sugar N-Acetyltransferase

Abstract: The yeast enzymes involved in UDP-GlcNAc biosynthesis are potential targets for antifungal agents. GNA1, a novel member of the Gcn5-related N-acetyltransferase (GNAT) superfamily, participates in UDP-GlcNAc biosynthesis by catalyzing the formation of GlcNAc6P from AcCoA and GlcN6P. We have solved three crystal structures corresponding to the apo Saccharomyces cerevisiae GNA1, the GNA1-AcCoA, and the GNA1-CoAGlcNAc6P complexes and have refined them to 2.4, 1.3, and 1.8 Å resolution, respectively. These structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
92
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(98 citation statements)
references
References 38 publications
6
92
0
Order By: Relevance
“…Based on substrate specificities, a number of major GNAT superfamily proteins have been identified, including histone NAT (HAT), aminoglycoside NAT (AAC), aaNAT, and glucosamine 6-phosphate NAT (gpNAT). We chose representative structures from the foregoing enzymes for a structural comparison: a HAT from yeast (MYST; PDB code 1fy7) (38), a HAT from Tetrahymena (Gcn5/ PCAF; PDB code 1puA) (39), human HAT (p300/CBP; PDB code 3biy) (40), a different HAT from yeast (Rtt109; PDB code 3qm0) (41), an AAC6 from Enterococcus faecium (PDB code 1n71) (42), an AAC6 from Salmonella enterica (PDB code 1s3z) (43), an AAC2 from Mycobacterium tuberculosis (PDB code 1m4g) (44), a gpNAT from Trypanosoma (PDB code 3i3g) (45), human gpNAT (PDB code 3cxs) (46), a gpNAT from Aspergillus fumigatus (PDB code 2vxk) (47), a gpNAT from yeast (PDB code 1i21) (48), and SNAT from O. aries (PDB code 1cjw) (49). Superposition of five GNAT structures and three mosquito aaNATs revealed that the common fold cores are nearly universally conserved (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Based on substrate specificities, a number of major GNAT superfamily proteins have been identified, including histone NAT (HAT), aminoglycoside NAT (AAC), aaNAT, and glucosamine 6-phosphate NAT (gpNAT). We chose representative structures from the foregoing enzymes for a structural comparison: a HAT from yeast (MYST; PDB code 1fy7) (38), a HAT from Tetrahymena (Gcn5/ PCAF; PDB code 1puA) (39), human HAT (p300/CBP; PDB code 3biy) (40), a different HAT from yeast (Rtt109; PDB code 3qm0) (41), an AAC6 from Enterococcus faecium (PDB code 1n71) (42), an AAC6 from Salmonella enterica (PDB code 1s3z) (43), an AAC2 from Mycobacterium tuberculosis (PDB code 1m4g) (44), a gpNAT from Trypanosoma (PDB code 3i3g) (45), human gpNAT (PDB code 3cxs) (46), a gpNAT from Aspergillus fumigatus (PDB code 2vxk) (47), a gpNAT from yeast (PDB code 1i21) (48), and SNAT from O. aries (PDB code 1cjw) (49). Superposition of five GNAT structures and three mosquito aaNATs revealed that the common fold cores are nearly universally conserved (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In this case, an active site base may not be required considering that the pK a of its substrate (ϳ7.75) is sufficiently low that a significant proportion will be in the chemically competent form at physiological pH (33). A very complex picture of catalysis emerges from these findings where the molecular details of acetyl transfer in the GNAT family depend on the specific enzyme and/or substrate.…”
mentioning
confidence: 96%
“…Removal of the C-terminal Met-454, Leu-455 of Nmt1p results in a 300 -400-fold reduction in the chemical transformation rate and converts the rate-limiting step of the enzyme from a step after chemical transformation to the transformation itself (47). In other GNAT members, a side chain carboxylate functions as a catalytic base to facilitate nucleophilic attack of a primary amino group on the thioester carbonyl of acetyl-CoA (50), although this role is assumed by the backbone carbonyl of Asn-134 in S. cerevisiae glucosamine-6-phosphate N-acetyltransferase 1 (51).…”
Section: Minireview: Protein N-myristoylation 39503mentioning
confidence: 99%